aión, kairós e chrónos. uma conversa sem fim sobre infância, filosofia e educação - kennedy, david knowles (2009)
In this dialogue between two interlocutors, the ontology of childhood is considered, first from the point of view of temporality, then power, then language, then from the perspective of philosophy, and inquires whether there is a specific philosophical and/or childlike dialectic of questioning and answering. The claim is made that both the philosopher and the artist carry a childlike way of questioning and acting on the world into adulthood. The discussion then moves to education, and considers the possibility of reconstructing the latter beyond the Platonic notions of “formation,” reproduction, discipline and subjection, and evaluates the role of philosophical dialogue in a school setting as an agent of transformation.